Perchloroethylene and Dry Cleaning: It's Time to Move the Industry to Safer Alternatives - Ceballos, Diana M.; Fellows, Katie M.; Evans, Ashley E.; Janulewicz, Patricia A.; Lee, Eun Gyung; Whittaker, Stephen G. (Frontiers in Public Health, 2021)
Perchloroethylene (PERC) is the most common solvent used for dry cleaning in the United States. PERC is a reproductive toxicant, neurotoxicant, potential human carcinogen, and a persistent environmental pollutant. The Environmental Protection Agency is evaluating PERC under the Frank R. Lautenberg Chemical Safety for the 21st Century Act, which amended the Toxic Substances Control Act (amended TSCA), and has mandated that PERC dry cleaning machines be removed from residential buildings. Some local and state programs are also requiring or facilitating transitions to alternative cleaning technologies. However, the potential for these alternatives to harm human health and the environment is not well understood. This review describes the issues surrounding the use of PERC and alternative solvents for dry cleaning while highlighting the lessons learned from a local government program that transitioned PERC dry cleaners to the safest current alternative: professional wet cleaning. Implications for future public health research and policy are discussed: 1) we must move away from PERC, 2) any transition must account for the economic instability and cultural aspects of the people who work in the industry, 3) legacy contamination must be addressed even after safer alternatives are adopted, and 4) evaluations of PERC alternatives are needed to determine their implications for the long-term health and sustainability of the people who work in the industry.